Polymer and two-dimensional inorganic compound compositely coated modified lithium battery positive electrode material as well as preparation method and application thereof
By using polymer and two-dimensional inorganic compound composite coating technology on the positive electrode material of lithium-ion batteries, a modified layer is formed to improve the cycle stability and high rate performance of the material, and the cycle life and rate of the positive electrode material under high nickel content are solved. The problem of poor performance achieves higher energy density and battery safety.
Patent Information
- Application Number
- CN202411333333.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The problems of the cathode materials of existing lithium-ion batteries with short cycle life and poor high-rate performance under high nickel content are mainly due to capacity attenuation and safety risks caused by structural collapse and chemical instability.
Using a modified lithium battery positive electrode material method that is coated with polymer and two-dimensional inorganic compounds, a modified layer is formed on the surface of ultra-high nickel positive electrode material, and a two-dimensional inorganic compound Ti3C2 and a polymer such as polyvinyl alcohol (PVA) reinforcement material is used. Adhesion and conductivity reduce side reaction losses and improve cycle stability and high rate performance.
It effectively improves the cycle life and high rate performance of the cathode material, enhances structural stability and chemical stability, extends the service life of the battery and improves the energy density.
Smart Images

Figure CN119252887A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound, and a preparation method and application thereof. Background Art
[0002] Fuel-powered vehicles are being phased out in favor of environmentally friendly electric vehicles (EVs) with low greenhouse gas emissions. However, they have not yet gained enough market share to replace internal combustion engine vehicles (ICEVs). This is mainly due to the lack of satisfactory performance of EVs. Driving range, charge rate capability, power performance, and life cycle characteristics are mainly determined by lithium-ion batteries (LIBs). In batteries, the cathode is one of the most important components as it mainly determines the performance and price of lithium-ion batteries. Currently, Li[Ni x Co y (Mn or Al) 1-x-y ]O2 (Mn=NCM or Al=NCA) cathode materials are used as typical cathodes in electric vehicle batteries, accounting for more than 65%-75% of electric vehicle batteries. However, due to the relatively low nickel content of the current layered oxide cathode series, they can only extract a limited reversible capacity (210 mAh g -1 ), which limits the range of driving electric vehicles.
[0003] In order to achieve higher energy density, many studies have focused on increasing the average Ni content in NCM or NCA cathodes to more than 90%. Increasing the Ni ratio can maximize the reversible capacity of the positive electrode; however, the insertion and extraction of a large number of lithium ions will cause structural collapse, and the cycle life and thermal safety will be severely affected by the rapid deterioration. These reliability issues are caused by the inherent structural and chemical instability of high-nickel layered positive electrodes. As the nickel content in the cathode increases, the degree of anisotropic unit cell volume change gradually increases, leading to the formation of intergranular cracks and intragranular cracks. Microcracks provide channels for electrolyte penetration and increase the internal surface area exposed to the electrolyte, accelerating the unstable Ni 4+ The parasitic reaction between ions and electrolyte forms a NiO-like rock salt layer on the periphery of the particles. The formation of the inert layer will seriously affect the transmission channel of lithium ions, thereby affecting the overall performance of the battery. In addition, this structural degradation will trigger the release of oxygen in the main structure, causing structural degradation, leading to battery expansion and possibly endangering battery safety. Summary of the invention
[0004] In view of the problems of short cycle life and poor high-rate performance of ultra-high nickel ternary materials, the purpose of the present invention is to provide a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound, and a preparation method and application thereof, so as to solve the problems of cycle stability, structural stability, capacity attenuation and rate performance of the positive electrode materials of lithium-ion batteries in the prior art.
[0005] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:
[0006] A method for modifying a lithium battery positive electrode material by composite coating of a polymer and a two-dimensional inorganic compound comprises the following steps:
[0007] (1) dispersing the ultra-high nickel positive electrode material in 10-30 ml of anhydrous ethanol, and fully dispersing it under the action of ultrasound to form a positive electrode dispersion;
[0008] (2) grinding the pre-freeze-dried Ti3C2 and slowly adding it to the positive electrode dispersion to obtain a mixed dispersion, and the addition amount is 1-5wt%;
[0009] (3) slowly adding the polymer to the mixed dispersion in step (2) to a final concentration of 1-3%, placing on a stirring heating table until the solvent evaporates, and drying to obtain a composite coated ultra-high nickel material;
[0010] (4) Centrifuging the composite-coated ultra-high nickel material, washing the excess residual lithium and the coating material, and then sieving to obtain a modified lithium battery positive electrode material composite-coated with a polymer and a two-dimensional inorganic compound.
[0011] As an improvement, in step (1), the chemical formula of the ultra-high nickel positive electrode material is LiMO2, wherein M refers to NixCoyMnz, wherein x≥0.6-0.9, y+z≤0.4, and x+y+z=1,0 <x<1,0<y<1,0<z<1。
[0012] As an improvement, the ultra-high nickel positive electrode material is LiNi 0.9 Co 0.05 Mn 0.05 O2.
[0013] As an improvement, in step (1), the frequency of the ultrasound is 20 KHz, the ultrasound time is 20-30 min, and the action temperature of the ultrasound is 25°C.
[0014] As an improvement, in step (2), the Ti3C2 is nano-scale multi-layered, and the thickness after grinding is less than 50 nm, and the speed of slowly adding the ground Ti3C2 is 1 mg / min.
[0015] As an improvement, in step (3), the final concentration of the polymer solution is 1%-2%, the temperature of the stirring heating table is 35° C., the stirring speed is 380 rpm, and the stirring time is controlled within 6 h.
[0016] As an improvement, in step (3), the polymer is polymethyl methacrylate (PMMA), polyethyleneimine (PEI), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE) or polyethylene glycol (PEG).
[0017] As an improvement, in step (4), the centrifugal speed is 5000 rpm and the centrifugal time is 5 min.
[0018] As an improvement, in step (5), the sieve sizes are 50, 100, and 300 meshes, respectively.
[0019] Any of the above-mentioned modified lithium battery positive electrode materials compositely coated with a polymer and a two-dimensional inorganic compound is characterized in that the modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound includes an ultra-high nickel positive electrode material, and a modification layer composed of a polymer and a two-dimensional inorganic compound (Ti3C2) coated on the ultra-high nickel positive electrode material, wherein the thickness of the modification is 10 to 50 nm.
[0020] The application of the modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound in lithium-ion batteries.
[0021] Ultra-high nickel ternary positive electrode materials have large theoretical specific capacity and high energy density, but as the nickel content increases, their cycle stability and structural stability will decrease. The two-dimensional inorganic compound (Ti3C2) itself has high conductivity. It is used as a coating layer to coat the surface of the ultra-high nickel material, thereby improving the capacity of the ultra-high nickel ternary positive electrode material at high rates. At the same time, the two-dimensional inorganic compound (Ti3C2) as an intermediate layer can reduce the loss of active materials due to severe side reactions and improve the cycle life of the material. The polymer polyvinyl alcohol (PVA) synergistically enhances the adhesion between the two-dimensional inorganic compound and the ultra-high nickel ternary material, making the two-dimensional inorganic compound more uniformly, densely and orderly coated on the surface of the ultra-high nickel ternary material. In addition, the polymer itself has good chemical stability, thermal stability and conductivity, which further improves the cycle stability and capacity of the composite modified positive electrode material.
[0022] Beneficial effects:
[0023] Compared with the prior art, the present invention discloses a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound, and a preparation method and application thereof. Based on the sol-gel method combined with the action of an ultrasonic external field, polyvinyl alcohol (PVA) and a two-dimensional inorganic compound (Ti3C2) are compositely coated on the surface of an ultra-high nickel ternary material as the core to reduce the loss of active materials due to severe side reactions and improve the cycle life of the material. At the same time, the high conductivity of the two-dimensional inorganic compound (Ti3C2) is used to accelerate the lithium ion deintercalation process to improve the high-rate performance of the material. The obtained modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound effectively improves the cycle life and high-rate performance of the positive electrode material.
[0024] In addition, the present invention utilizes polyvinyl alcohol (PVA) with good chemical stability, thermal stability, and electrical conductivity to further improve the cycle stability and capacity of the composite modified positive electrode material. At the same time, during the coating process, the two-dimensional inorganic compound (Ti3C2) will form a certain Ti doping layer on the surface of the ultra-high nickel ternary positive electrode, ensuring the structural stability of the ultra-high nickel ternary positive electrode material to ensure stable capacity during the cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of modified lithium battery positive electrode materials compositely coated with polymers and two-dimensional inorganic compounds prepared in Example 1, Example 2, Comparative Example 1, and Comparative Example 5;
[0026] Figure 2 The polyvinyl alcohol (PVA) & two-dimensional inorganic compound (Ti3C2) / composite ultra-high nickel material (Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2@Ti3C2&PVA) energy spectrum;
[0027] Figure 3 The polyvinyl alcohol (PVA) & two-dimensional inorganic compound (Ti3C2) / composite ultra-high nickel material (Li[Ni 0.9 Co 0.05 Mn 0.05 ]TEM image of O2@Ti3C2&PVA);
[0028] Figure 4 Cycle diagrams of modified lithium battery positive electrode materials compositely coated with polymers and two-dimensional inorganic compounds prepared in Example 1, Example 2, Comparative Example 1, and Comparative Example 5;
[0029] Figure 5 These are rate diagrams of modified lithium battery positive electrode materials compositely coated with polymers and two-dimensional inorganic compounds prepared in Example 1, Example 2, Comparative Example 1, and Comparative Example 5. DETAILED DESCRIPTION
[0030] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0031] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0032] An embodiment of the present invention provides a method for modifying lithium battery positive electrode materials by composite coating of polymers and two-dimensional inorganic compounds, and an ultra-high nickel ternary positive electrode Li[Ni0.9Co0.05Mn0.05]O2@Ti3C2&PVA material compositely coated with polymer polyvinyl alcohol (PVA) and two-dimensional inorganic compound (Ti3C2).
[0033] Example 1
[0034] The first ultra-high nickel (Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2) The amount of ternary positive electrode material added is 3g, and the amount of two-dimensional inorganic compound (Ti3C2) added is 1wt%.
[0035] Under the action of an ultrasonic field with a frequency of 20 KHz, 3 g of high-nickel ternary cathode material (Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2), controlling the high nickel ternary material Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2 was added at a rate of 1 g / min. After the addition was completed, ultrasound was continued for 20 min to fully disperse it. The temperature was controlled at 25°C to obtain solution 1.
[0036] The solution 1 was transferred to a stirring heating table and stirred for 0.5 h. The temperature was controlled at 35 °C and the stirring speed was 380 rpm.
[0037] 30 mg (1 wt%) of freeze-dried two-dimensional inorganic compound (Ti3C2) was placed in a mortar and fully ground into fine flake particles, i.e., dispersed nano-scale multilayers with a thickness of less than 50 nm. To ensure sufficient grinding, 3 ml of deionized water was added during grinding, the grinding time was 30 min, and the temperature was controlled within 25°C during grinding.
[0038] The ground two-dimensional inorganic compound (Ti3C2) is slowly added to solution 1 to obtain a mixed dispersion, thereby obtaining solution 2.
[0039] A polyvinyl alcohol (PVA) solution with a concentration of 1% was prepared and slowly added into solution 2, and the amount of the polyvinyl alcohol (PVA) solution was controlled to be 3 ml, to form solution 3.
[0040] Solution 3 was stirred on a stirring heating table for 6 h until the solvent evaporated, the temperature was controlled at 35 ° C, the stirring speed was 380 rpm, and after drying, a mixed material that had not yet been completely coated was obtained, which was placed in a 60 ° C vacuum oven for drying, and the mixed material that had not yet been completely coated was obtained as the oven cooled.
[0041] The obtained mixed material that has not yet been coated is centrifugally cleaned at a speed of 5000rpm for 5min. To remove residual lithium and residual coating on the surface. After centrifugal cleaning, it is placed in a 60°C vacuum oven for drying, and the mixed material that has not yet been coated is obtained as the oven cools. It is then sieved, and the sieve sizes are 50 mesh, 100 mesh, and 300 mesh, respectively. After the sieving is completed, a polymer and two-dimensional inorganic compound composite coated modified lithium battery positive electrode material is obtained, that is, a high-nickel ternary composite positive electrode Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2@Ti3C2&PVA-1% material.
[0042] Example 2
[0043] The addition amount of the two-dimensional inorganic compound (Ti3C2) was changed to 3wt%, and the rest was the same as in Example 1, and finally an ultra-high nickel ternary composite positive electrode Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2@Ti3C2&PVA-3% material.
[0044] Example 3
[0045] The addition amount of the two-dimensional inorganic compound (Ti3C2) was changed to 5wt%, and the rest was the same as in Example 1, and finally a high-nickel ternary composite positive electrode Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2@Ti3C2&PVA-5% material.
[0046] The amount of two-dimensional inorganic compound (Ti3C2) added directly affects the coating effect. When the amount of Ti3C2 coated is too small, the protective layer formed on the surface of the positive electrode material may be discontinuous or incomplete, which will result in more contact between the electrolyte and the electrode material, and thus cannot effectively prevent the surface erosion and structural damage of the electrode material. Due to the insufficient protective layer, the battery may have a higher interface impedance during the charge and discharge process, which directly affects the charging efficiency and cycle life of the battery. In addition, if the coating layer cannot effectively coat the surface of the high-nickel material, nickel may be dissolved, thereby reducing the chemical stability and safety of the battery. When the amount of Ti3C2 coated is too much, although it can more effectively block the contact between the electrolyte and the electrode material, the overly thick coating layer may hinder the migration of lithium ions. Too much coating material may lead to a decrease in the activity of the electrode material because it may hinder the effective lithium ion exchange between the electrode surface and the electrolyte. An overly thick protective layer may also increase the internal resistance of the battery, affecting the energy density and power output of the battery. The appropriate coating amount should be able to form a uniform and continuous protective layer without affecting the electrochemical activity of the material itself. The appropriate amount of Ti3C2 coating can effectively isolate the contact between the electrode material and the electrolyte, reduce the interface corrosion during the charge and discharge process, thereby improving the cycle performance of the battery and enhancing its electrochemical stability. At the same time, the appropriate amount of coating also helps to provide more conductive paths and improve the rate performance of the battery.
[0047] It can be seen from the above results that when the addition amount of the two-dimensional inorganic compound (Ti3C2) in the present invention is 3wt%, the structure of the obtained material is stable and the material is excellent.
[0048] Comparative Example 1
[0049] The same procedures as in Example 1 were followed except that 300 mg (10 wt%) of a two-dimensional inorganic compound (Ti3C2) was added for coating modification.
[0050] If too much two-dimensional inorganic compound (Ti3C2) is added, the ultra-high nickel ternary cathode material Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2 surface accumulates a large amount of two-dimensional inorganic compounds (Ti3C2), which makes the lithium ion transmission path excessively long, causing serious obstacles to its deintercalation process, resulting in a significant increase in impedance. At the same time, since the concentration and amount of polyvinyl alcohol (PVA) are much smaller than the amount of two-dimensional inorganic compounds (Ti3C2) added, this will make it impossible for the two-dimensional inorganic compounds (Ti3C2) to fit tightly on the ultra-high nickel ternary positive electrode material Li[Ni 0.9 Co 0.05 Mn 0.05] The surface of O2 causes the two-dimensional inorganic compound (Ti3C2) to accumulate or disperse in the electrode piece, which reduces the proportion of active materials in the electrode, resulting in a decrease in capacity and an increase in rate performance, making it impossible to meet performance requirements.
[0051] Comparative Example 2
[0052] The same method as in Example 1 is used except that the concentration of polyvinyl alcohol (PVA) added is changed from 1% to 5%.
[0053] If the concentration of polyvinyl alcohol (PVA) is too high, it may cause the high nickel ternary cathode Li[Ni 0.9 Co 0.05 Mn 0.05 ] An overly thick polymer coating is formed on the surface of the O2 material. Due to the general conductivity of the polymer, an overly thick polymer layer will reduce the conductivity of the surface of the ultra-high nickel positive electrode material and increase its interfacial transfer impedance (Rct), which will seriously hinder the insertion and extraction process of lithium ions on the positive electrode surface, thereby affecting the overall rate performance and capacity of the material, resulting in problems such as performance not meeting the requirements.
[0054] Comparative Example 3
[0055] The same procedures as in Example 2 were followed except that only 90 mg (3 wt%) of the two-dimensional inorganic compound (Ti3C2) was added and polyvinyl alcohol (PVA) was not added.
[0056] If only two-dimensional inorganic compounds (Ti3C2) are added during the coating process without adding polyvinyl alcohol (PVA) for auxiliary coating, the coating effect will not meet expectations. The two-dimensional inorganic compound (Ti3C2) may be free outside the surface of the ultra-high nickel positive electrode material, causing coating failure, and thus failing to achieve the effects of improving the rate performance, capacity, and interface stability of the ultra-high nickel positive electrode material during the cycle.
[0057] Comparative Example 4
[0058] Except that the two-dimensional inorganic compound (Ti3C2) and polyvinyl alcohol (PVA) are not added, the remaining steps are the same as those in Example 1, that is, the bare high-nickel ternary positive electrode material Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2.
[0059] If the ultra-high nickel ternary cathode material is not coated and modified, its capacity will drop rapidly and the voltage decay will accelerate during long-term cycling at high voltage. 4+The high chemical activity of the battery will react with the electrolyte, causing structural degradation, dissolution of transition metal elements, and escape of oxygen atoms to produce oxygen, which will cause serious consequences such as high battery temperature, flatulence, and failure, making the battery unable to achieve its expected life.
[0060] Figure 1 These are the XRD spectra of Example 1, Example 2, Comparative Example 1, Comparative Example 4, and the two-dimensional inorganic compound (Ti3C2). It can be observed that with the increase of the coating content of the two-dimensional inorganic compound (Ti3C2), the characteristic peak of the two-dimensional inorganic compound (Ti3C2) in the XRD spectrum continues to increase. The uncoated Comparative Example 4 does not have the characteristic peak of the two-dimensional inorganic compound (Ti3C2). The amount of two-dimensional inorganic compound (Ti3C2) added in Comparative Example 1 is the largest, and its characteristic peak of the two-dimensional inorganic compound (Ti3C2) is also stronger. At the same time, Example 1, Example 2, Comparative Example 1, and Comparative Example 4 show typical structural characteristics of LiNiO2 positive electrode materials, and their diffraction peaks are characteristic peaks of a-NaFeO2 layered structure, belonging to the hexagonal crystal system, R-3m space group, and the two pairs of diffraction peaks (006) / (012) and (018) / (110) are obviously split, forming a better layered structure. The diffraction peaks of the materials before and after coating do not change significantly, and there are no impurity peaks. The peak intensity ratio of (003) to (104) is comparable to that of the layered positive electrode material Li + / Ni 2+ The peak intensity ratio I(003) / I(104) is smaller than that of Example 1 and Example 2, indicating that the Li + / Ni 2+ This is because during the coating process, the Ti element in the two-dimensional inorganic compound (Ti3C2) will be doped into the surface of the ultra-high nickel ternary positive electrode material, inhibiting the Ni 2+ The generation of Li + / Ni 2+ However, with the increase of two-dimensional inorganic compounds (Ti3C2), the doping of Ti will also increase accordingly, which will aggravate the Li+ / Ni 2+ Mixed.
[0061] Figure 2-3 The EDS and TEM images of Example 2 clearly show that with the help of 1% polyvinyl alcohol (PVA), the two-dimensional inorganic compound (Ti3C2) is tightly and evenly coated on the surface of the ultra-high nickel ternary material. At the same time, the EDS image also shows that the Ti element is doped into the ultra-high nickel ternary material during the coating process, and these surface two-dimensional inorganic compounds (Ti3C2) & polyvinyl alcohol (PVA) are successfully coated on the ultra-high nickel ternary material.
[0062] Figure 4 It is the cycle diagram of Example 1, Example 2, Comparative Example 1, and Comparative Example 4 at 25°C and 2.7-4.5V. Among them, the capacity retention rates of Example 1 and Example 2 are 83.75% and 96.75%, respectively, showing excellent cycle retention rates and high capacity improvement. This is because the two-dimensional inorganic compound (Ti3C2) as an excellent lithium ion and electron transport layer can ensure the smooth extraction and embedding process of lithium ions and ensure the capacity improvement. At the same time, the two-dimensional inorganic compound (Ti3C2) has excellent chemical stability, which can ensure that the ultra-high nickel cathode material is not corroded by the electrolyte and ensure the integrity of the surface structure of the material.
[0063] Figure 5 The figure is the rate diagram of Example 1, Example 2, Comparative Example 1 and Comparative Example 4 at 25°C and 2.7-4.5V. Among them, under the high rate condition of 10C, Example 1 and Example 2 show 130mAh·g -1 and 148mAh g -1 The capacity of Comparative Examples 1 and 4 is only 110 mAh g -1 and 118 mAh g -1 . This is because at high rates, the reaction will be more rapid and cannot be fully carried out, which will cause the side reactions to intensify and the lithium ions to be unable to be fully embedded and removed, resulting in lower capacity. However, the presence of the two-dimensional inorganic compound (Ti3C2) can ensure that the ultra-high nickel material can still exert its capacity at high rates. The specific addition ratio further promotes the use of capacity. As shown in Example 2, after forming a suitable coating amount of two-dimensional inorganic compound (Ti3C2) and a polyvinyl alcohol (PVA) coating layer at a suitable concentration, it will be beneficial to the transmission of lithium ions and ensure that the capacity is fully utilized.
[0064] The above is only a specific implementation of the present application. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. The protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound, characterized in that: The following steps are involved: (1) Dispersing the ultra-high nickel positive electrode material in 10-30 ml of anhydrous ethanol, and fully dispersing it under the action of ultrasound to form a positive electrode dispersion; (2) Grind the pre-freeze-dried Ti3C2 and slowly add it to the positive electrode dispersion to obtain a mixed dispersion, and the addition amount is 1-5 wt%; (3) slowly adding the polymer to the mixed dispersion in step (2) to a final concentration of 1-3%, placing on a stirring heating table until the solvent evaporates, and drying to obtain a composite coated ultra-high nickel material; (4) The ultra-high nickel material after composite coating is centrifuged, the excess residual lithium and coating material are cleaned, and then sieved to obtain a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound.
2. The method for preparing a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound according to claim 1, characterized in that: In step (1), the chemical formula of the ultra-high nickel positive electrode material is LiMO2, wherein M refers to Ni x Co y Mn z , where x ≥ 0.6-0.9, y + z ≤ 0.4, and x+y+z = 1, 0 <x<1,0<y<1,0<z<1。 3. The method for preparing a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound according to claim 2, characterized in that: The ultra-high nickel positive electrode material is LiNi 0.9 Co 0.05 Mn 0.05 O2.
4. The method for preparing a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound according to claim 2, characterized in that: In step (1), the frequency of the ultrasound is 20 KHz, the ultrasound time is 20-30 min, and the action temperature of the ultrasound is 25 °C.
5. The method for preparing a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound according to claim 2, characterized in that: In step (2), the Ti3C2 is in nano-scale multi-layered form, and the thickness after grinding is less than 50 nm, and the speed of slowly adding the ground Ti3C2 is 1 mg / min.
6. The method for preparing a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound according to claim 2, characterized in that: In step (3), the final concentration of the polymer solution is 1%-2%, the temperature of the stirring heating table is 35°C, the stirring speed is 380 rpm, and the stirring time is controlled within 6 hours; the polymer is polymethyl methacrylate, polyethyleneimine, polyacrylonitrile, polytetrafluoroethylene or polyethylene glycol.
7. The method for preparing a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound according to claim 2, characterized in that: In step (4), the centrifugal speed is 5000 rpm and the centrifugal time is 5 min.
8. The method for preparing a modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound according to claim 2, characterized in that: In step (5), the sieve sizes are 50, 100, and 300 meshes, respectively.
9. A modified lithium battery positive electrode material based on a composite coating of a polymer and a two-dimensional inorganic compound according to any one of claims 1 to 8, characterized in that: The modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound comprises an ultra-high nickel positive electrode material and a modification layer composed of a polymer and a two-dimensional inorganic compound (Ti3C2) coated on the ultra-high nickel positive electrode material, wherein the thickness of the modification is 10 to 50 nm.
10. Application of the modified lithium battery positive electrode material compositely coated with a polymer and a two-dimensional inorganic compound according to claim 9 in lithium ion batteries.
Citation Information
Patent Citations
Nickel-cobalt lithium manganate high-nickel ternary positive electrode material for lithium battery and preparation method of nickel-cobalt lithium manganate high-nickel ternary positive electrode material
CN116885135A
Positive electrode material and application thereof
CN118073536A
Composite lithium iron phosphate material as well as preparation method and application thereof
CN118104007A
High-nickel NCM ternary positive electrode material and preparation method and application thereof
CN118281195A
Preparation method for polymer / lithium nickel manganese oxide composite material, and product and use thereof
WO2024016467A1
